2023
DOI: 10.3390/su152316441
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Creative Economy Applying the Contingent Valuation Method: A Case Study on the Greek Cultural Heritage Festival

Aikaterini Koumoutsea,
Paraskevi Boufounou,
George Mergos

Abstract: The effectiveness of the economic policies implemented by a country/region directly affects its economic growth potential. Cultural Heritage Festivals are a sector of the creative economy that, by promoting culture, may have a significant impact on national/regional sustainable economic development. This study assesses the implementation of the Contingent Valuation Method (CVM) and the estimation of the Willingness To Pay (WTP) demand curve, using data collected for the Kalamata Dance Festival as a case study,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 61 publications
0
1
0
Order By: Relevance
“…This research study found that the multiplier of creative industries in Ukraine is equal to 1.9-2.2, which significantly impacts Ukraine's economy. In 2023, Koumoutsea evaluated the creative economy by applying the CVM to the Greek Cultural Heritage Festival, and they found that the festival has the potential to drive Greece's GDP in the future (Koumoutsea et al 2023). According to research which examined the impact of the creative industries on local economic development in Ukraine, these sectors can generate employment in the country at a rate of 1.91% annually and contribute 3.47% to the national GDP (Pavliuk 2023).…”
Section: Literature Reviewmentioning
confidence: 99%
“…This research study found that the multiplier of creative industries in Ukraine is equal to 1.9-2.2, which significantly impacts Ukraine's economy. In 2023, Koumoutsea evaluated the creative economy by applying the CVM to the Greek Cultural Heritage Festival, and they found that the festival has the potential to drive Greece's GDP in the future (Koumoutsea et al 2023). According to research which examined the impact of the creative industries on local economic development in Ukraine, these sectors can generate employment in the country at a rate of 1.91% annually and contribute 3.47% to the national GDP (Pavliuk 2023).…”
Section: Literature Reviewmentioning
confidence: 99%